Интеграция процедуры нормирования и учета горюче-смазочных материалов в систему виртуального предприятия автомобильного транспорта - Волков, Владимир Петрович; Кривошапов, С. И. (НТУ "ХПИ", 2015)
В статье предложена система программных и аппаратных средств по определению расчетных и фактических значений расхода топлива транспортных машин. Рассмотрены принципы построения автоматической системы управления на предприятиях автомобильного транспорта. Проанализированы способы и технические средства измерения расхода топлива в условиях движении автомобиля. Приведены принципы построения разработанной программы по нормированию и учету горюче-смазочных материалов. Дано описание структуры программы и базы данных. Указаны пути интеграции разработанного программного обеспечения в единую информационную среду виртуального предприятия.

The paper proposes a system of hardware and software to determine the calculated and actual values of fuel consumption vehicles. The principles of building automatic control systems for road transport enterprises. For operational management and obtain information about the state of machines is proposed to use the wireless positioning system and data communication. Explore ways and technical means measuring of fuel consumption in the conditions of driving. Developed principles of building program for rationing and accounting of fuel and lubricants. The main parameters of the route, such as: coordinates of the destinations and operation time and distance on the route and the average speed and fuel consumption, is removed with a GPS-tracker and is transmitted to the processing center by GSM communication channel. Given a description of the structure of the program and database. Were developed the ways of integration of the software into a unified information environment of virtual enterprise. Actual and theoretical fuel used to evaluate the technical condition of the vehicle and the planning of prophylactic and repair works. The results program operation are used to calculate the the technical and economic and financial performance indicators company.
Integration of regulation and registration procedures of fuels and lubricants in virtual enterprise of road transport
Keywords: расход топлива; нормирование топлива; автомобили; программное обеспечение; компьютерные сети; навигация; датчики расхода топлива; companies of road transport; fuel consumption; fuel rationing; cars; software; computer networks; navigation; sensors of fuel consumption